The Effectiveness of Softbook Media on The Religious Values of B1 Children - Erika Dwiyani; Nurhayati; Sita Awalunisah; Durrotunnisa; Marcella Siduan; Vitha Aulia Safitri (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
This research is motivated by the low development of early childhood religious values caused by the use of learning media that is less interesting and less interactive. This study aims to determine the development of children's religious values, the application of softbook media, and the effectiveness of the use of softbook  media in developing children's religious values in Group B1 of Kindergarten Cendekia Tadulako. The research method used was quantitative with a quasi experiment  type using a one group pretest-posttest design. The subjects of the study were 20 children. Data collection techniques are carried out through observation, interviews and documentation, while data analysis uses a t-test (paired sample t-test). The results of the study showed that there was an increase in the development of children's religious values by 25% from pretest to posttest results. In detail, the increase in the aspect of knowing ablution before prayer is 25%, knowing hijaiyah letters by 28%, and knowing Allah's creation by 25%. The results of the hypothesis test showed a significance value of 0.000<0.05, which means that the use of softbook  media is effective in developing children's religious values. Thus, it can be concluded that softbook  media is effectively used as a learning medium to increase the religious value of early childhood education.